Environmental values and willingness to pay for a protected area: a segmentation of Italian university students. Issue 1 (2nd January 2019) - Forleo, M. B.; Romagnoli, L.; Palmieri, N.
ABSTRACT: The study investigated students' attitudes and willingness to pay (WTP) for the protection of some environmental values. The empirical study refers to a site located in Southern Italy and inserted into the Natura 2000 European Network. Students were segmented according to their appreciation of environmental values and the WTP for them. We considered two scenarios of the study site – of use and non-use – and four values – recreational, educational, bequest and existence. Five clusters, from the 'unconcerned' to the 'committed' one, reveal a diversity of profiles across the sample. Segmentation results point out the multifunctionality of the environmental heritage and highlight the heterogeneity of students' environmental profiles.